Peran Perencanaan Pembelajaran dalam Meningkatkan Kualitas Pengajaran - Nadlir, Nadlir; Khoiriyatin, Vilda Zahrotul; Fitri, Berliana Aulia; Ummah, Durroh Nasihatul (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study aims to analyze the role of lesson planning in improving teaching quality. Lesson planning is a very important role to improve the quality of teaching, because in it there are many possibilities for teachers to develop learning strategies that are more active and more efficient. This research uses library research methods, methods carried out by searching for data and information through sources available in libraries, such as books, magazines, documents, historical records, or other research relevant to the object of research, which in this study discusses the role of lesson planning in improving teaching quality. In this study we will find out how lesson planning can improve the quality of teaching by improving the teacher's ability to develop material, increase student participation, and improve learning outcomes. The results of this study are expected to contribute to the development of education and improve the quality of teaching.